The effectiveness of management training programs: A meta-analytic review - Matias Busso; Kyunglin Park; Nicolás Irazoque (Inter-American Development Bank (IDB), 2023)
We conduct a meta-analysis of 44 studies and 68 different managerial skills training programs, with the aim of identifying program characteristics that can lead to more effective public policies promoting firm growth and entrepreneurship. We synthesize 431 estimates to assess the effects of these programs on firm performance. Our findings show that, on average, managerial skills development programs have positive returns on management practices, firm productivity, profits, and survival. We also examine how program and participant specifications affect program effectiveness. Our analysis suggests that, on average, business training programs focused on human resources, soft skills, marketing, and finance-accounting, especially when organized by local organizations, tend to result in better firm performance. Moreover, training of potential entrepreneurs and managers in specifically targeted sectors such as agriculture, manufacturing, or services was more likely to result in improvement compared to non-targeted programs. Finally, our results indicate that programs that involve both male and female participants are more likely to enjoy higher effects from managerial training interventions.
Keywords: J24; L25; M13; 330; Managerial skills; Firm performance; Entrepreneurship; Meta-analysis